DETERMINANTS OF ENTREPRENEURIAL INTENTION: The Case of Norwegian Students - Indarti, Nurul; Krinstiansen, Stein (Gadjah Mada International Journal of Business, 2003)
This paper aims to identify determinants of entrepreneurial intentions among young people. The empirical basis is Norwegian students, while an objective is also to create a basis for comparative studies among different economic and cultural contexts. Independent variables in the study include demographic factors and individual background, personality traits, and contextual elements like access to capital and information. The individual perceptions of self-efficacy and instrumental readiness are the variables that affect entrepreneurial intentions most significantly. Age, gender and educational background have no statistically significant impact. Generally, the level of the entrepreneurial intentions among Norwegian students is relatively low, which may be explained by social status and economic remuneration of entrepreneurs compared with employees in the Norwegian context.